Projection of Body as Repulsion to Subjugated Female Identity in Mahasweta Devi’s Breast Giver and Parijat’s The Raped Tears of Salgi - Nepal, Khagendra Prasad (KMC Research Journal, 2020)
This paper seeks to analyze how the projection of female body stands as a great repulsion to the female identity that is defined by the male chuavinism with particular reference to the two stories of two prominent writers Mahasweta Devi of India and Parijat of Nepal. One story, Breast Giver, of Mahasweta Devi and a story, The Raped Tears of Salgi, of Parijat have got a keen observation dealing with the female body alienation. This study shows how female bodies have been alienated from their selves; how these female characters Jashoda and Salgi do not have the sense of being distanced from their own selves. The study adopts qualitative methodology and takes Marxist feminism as a theoretical tool to interpret and analyze the primary text. Instead of focusing on the analysis of the theme of the text, the study focuses on analysis of the text in concern with female body portrays in the stories. The female characters are physically assaulted, raped, and coerced time and again. Their bodies become the site where men enact violence. The study argues that these female characters become the victim of violence just because they are women. The study makes an attempt to make people understand how women suffer from gender-based violence in patriarchy.